2023
DOI: 10.1093/infdis/jiac293
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches to Understand Cognitive Phenotypes in People With HIV

Abstract: Cognitive disorders are prevalent in people with HIV (PWH) despite antiretroviral therapy. Given the heterogeneity of cognitive disorders in PWH in the current era and evidence that these disorders have different etiologies and risk factors, scientific rationale is growing for using data-driven models to identify biologically defined subtypes (biotypes) of these disorders. Here, we discuss the state of science using machine learning to understand cognitive phenotypes in PWH and their associated comorbidities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Neurocognitive impairment (NCI) remains prevalent among people with HIV despite suppressive ART [22,23]. Mechanisms underlying HIV-associated neurocognitive disorders (HAND), which include asymptomatic neurocognitive impairment (ANI), minor neurocognitive disorder (MND), and HIV-associated dementia (HAD), in ART-treated individuals are multifactorial and include ongoing low-level viral replication in the brain, neuroinflammation, ART neurotoxicity, cerebrovascular disease, and other factors [2,[22][23][24][25]. Although HIV encephalitis (HIVE) is common in untreated HIV+ individuals, it is uncommon in virally suppressed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Neurocognitive impairment (NCI) remains prevalent among people with HIV despite suppressive ART [22,23]. Mechanisms underlying HIV-associated neurocognitive disorders (HAND), which include asymptomatic neurocognitive impairment (ANI), minor neurocognitive disorder (MND), and HIV-associated dementia (HAD), in ART-treated individuals are multifactorial and include ongoing low-level viral replication in the brain, neuroinflammation, ART neurotoxicity, cerebrovascular disease, and other factors [2,[22][23][24][25]. Although HIV encephalitis (HIVE) is common in untreated HIV+ individuals, it is uncommon in virally suppressed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…First, there are two construct that, while overlapping, represent distinct aspects of cognition. A recent NIMH-sponsored meeting on biotypes of CNS complications in persons living with HIV highlighted the heterogeneity of manifestations of neuro-HIV [ 30 ] and the presence of self-reported cognitive difficulties may represent one phenotype of brain involvement. We did not test the association between biomarkers of gut permeability and a diagnosis of HAND for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…and report them as symptoms, while individuals with HAD present severe cognitive deficits. Despite this categorization attempt, there are studies arguing that the pattern of cognitive impairment is inconsistent among individuals [18,23,24]. In addition, a recent longitudinal study focusing on the progression of NCI found that HAND might not advance invariably [25].…”
Section: Neuropsychological Assessments 21 Understanding Neurocogniti...mentioning
confidence: 99%